A Study On Service Convergence Within A Wireless Metropolitan Area Network (MAN) In Malaysia - Tan, Roy Yew Hoong (2005)
The main purpose of this paper is to identify and provide a feasible solutions with which Internet, high-speed connections, wireless technology and service convergence can be unified to meet the demands of today's information technology industry.